Towards zero energy architecture : new solar design - Guzowski, Mary. (London : Laurence King, 2010)
Explores the theories, practices and principles of fresh approaches to solar architecture that foster both design excellence and low-energy use. This book analyses ten awardwinning buildings, focusing on the details of the design strategy, the impact of local climate and the importance of seasonal changes in sunlight and wind strength.
Introduction Chapter 1: Fostering an ecological vision First LivingHome Model Home, Santa Monica, California, USA, Ray Kappe Architects/Planners and LivingHomes Kingspan Lighthouse, Watford, UK, Sheppard Robson Chapter 2: Prioritizing passive design Solarsiedlung am Schlierberg, Freiburg, Germany, Rolf Disch Architects Aldo Leopold Legacy Center, Baraboo, Wisconsin, USA, The Kubala Washatko Architects Chapter 3: Defining an ethic of enough Tim and Karen Hixon (Government Canyon) Visitor Center, Helotes, Texas, USA, Lake|Flato Architects SOLTAG Energy Housing, HA rsholm, Denmark, Nielsen and Rubow, Cenergia, Kuben Byfornyelse Danmark, and Velux Danmark Chapter 4: Using responsive envelopes Rozak House, Lake Bennett, Northern Territory, Australia, Troppo Architects Year 2015 Prototype Home-Made in Germany, Technische Universitat Darmstadt, Germany Chapter 5: Expressing an ecological aesthetic Steinhude Sea Recreational Facility, Steinhude, Germany, Randall Stout Architects and Archimedes GmbH Sino-Italian Ecological and Energy Efficient Building (SIEEB), Tsinghua University, Beijing, China, Mario Cucinella Architects
Includes bibliographical references (p. 202-203) and index.
Keywords: Architecture and solar radiation; Solar buildings -- Design and construction; Architecture and energy conservation; Architecture -- Environmental aspects